Answer:
3
Step-by-step explanation:
I say it is 3 because 2 * 3 = 6
6/2=3
I hope this helps you:)
6 times 1 =6
2 times x =6
x=3
In system A, the first equation multiply by 4
8x - 4y = 12 (1st)
3x + 4y = 10 (2nd)
--------------------add
11x = 22
So answer is B.
Answer:
True
Step-by-step explanation:
The definition of the function is a relation with exactly one x for each y. x is the domain, and y is the range, so all functions have a domain and a range.
The answer would be A. 4
Here’s what I would do.
Multiply both sides by 12 so u can get m- 2 by itself.
m-2= 2
How’d I get the two? It comes from when I multiplied 12 on both sides. 12/6= 2
Now ur equation should be
m-2=2
Do the opposite and add two to both sides to get the variable by itself.
m=4
Hope this helps :)))